The Utilization of Regional Language-Based Communication as a Marketing Strategy for MSME Products in the Wakatobi Traditional Market - Cony; Astil Harli Roslan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the regional economy, including in Wakatobi Regency. One of the main challenges for MSMEs in traditional markets is the limitations of effective and contextual marketing strategies with local culture. This study aims to examine the use of regional language-based communication as a marketing strategy for MSME products in the traditional market of Wakatobi. The research method used is a qualitative approach with observation, interview, and documentation techniques for MSME actors, consumers, and market managers. The results of the study show that the use of regional languages in buying and selling interactions is able to increase emotional closeness, consumer trust, and customer loyalty. Thus, regional language-based communication can be an effective and sustainable marketing strategy for MSMEs in the traditional Wakatobi market.